Influence Of Islamic Branding On Brand Resonance Of Nestlé: A Comparative Study Between Malaysia And Pakistan - Bukhari, Syeda Nazish Zahra (2021)
The Muslim consumer market has recently emerged as an attractive consumer market for global brands due to their growing numbers and purchasing power. However, the brands targeting Muslim consumers occasionally face various forms of anti-consumption behaviours stemming from perceived brand-religious incongruity. The lack of brand resonance makes the brand vulnerable towards negative consumer perceptions since it is connected to the absence of an emotional connection between the brands and Muslim consumers. This study examines Islamic branding as a strategy for creating brand resonance in Islamic brands. The research framework is based on the theory of self-congruity and the Customer-Based Brand Equity (C.B.B.E) pyramid. The three antecedents, i.e., religiosity, brand knowledge, and Islamic Corporate Social Responsibility (ICSR), are proposed based on the C.B.B.E pyramid. This study is comparative in nature conducted between Muslim consumers in Malaysia and Pakistan due to the varying percentage of Muslim consumers in both countries and differences in the development of Islamic branding in both geographic regions. Eight hypotheses are developed based on the study's research objectives and questions. Data is collected from three major cities of Malaysia and Pakistan through purposive sampling. A total sample size of 649 respondents (326 from Malaysia and 323 from Pakistan) was collected through self-administered questionnaires.